TRENDS AND CONSEQUENCES OF THE VARIATION IN FUEL PRICES IN THE TRANSPORTATION SECTOR IN CIUDAD DEL ESTE - Daniel Cuenca Cárdenas, Gustavo; Báez Maidana, Nicolás; Nicolás Vargas Bogado, Sergio; Vargas Rivas, Osvaldo; Díaz Benítez, Sinecia (Revista Gênero e Interdisciplinaridade, 2023)
The main objective of this study is to investigate and analyze the Trends and Consequences of the Variation in Fuel Prices in the Transportation Sector in Ciudad del Este. During recent years, fuel prices have suffered variations and increases that have disadvantaged to society in general. This research focuses on the transportation sector in Ciudad del Este. The methodology used is research under the Quantitative approach, with a descriptive scope, data collection was carried out through a survey.The results have shown that for transporters, the rise in fuel prices has had a negative impact in recent years. To counteract this phenomenon, they resort to strategies to confront its negative effects.As a result of the investigation, it has been determined that transporters have adapted to counteract the negative aspects of the rise in fuel prices.